Visual Persuasion: Assessing the Influence of Political Posters on Voter Behavior of Bangladesh - Uddin, Md Forhad; Nuha, Tabassum; Belal, Mohammad; Tabassum, Maliha (Informasi, 2025)
Political posters play a significant role in shaping voter perceptions and behaviors in Bangladesh, employing visual elements such as color, design, and symbolism to effectively communicate messages and resonate emotionally with diverse electorate groups. This study investigates the influence of these posters on voter behavior toward political candidates and parties, drawing on established theoretical frameworks like the Elaboration Likelihood Model (ELM). Through a survey-based approach, our findings reveal that posters exert substantial influence, with a majority of respondents acknowledging their role in shaping political opinions. Emotional appeals embedded in posters are shown to sway voter decisions, emphasizing the posters' effectiveness in engaging voters through both central and peripheral routes of persuasion. Moreover, the study highlights posters' enduring impact beyond elections, contributing to sustained political attitudes and fostering democratic engagement in Bangladesh's socio-political landscape. By aligning with existing literature on visual persuasion and political communication, this research underscores the critical role of posters as powerful tools in influencing public opinion and promoting civic participation.   Keywords: political poster, persuasion, voter behavior, Bangladesh, civic participation